Three dimensional dynamic response of underground openings in saturated rock masses. - Kim, Sun-Hoon
In this paper a three dimensional dynamic analysis program for saturated porous rocks and soils is presented. The theoretical formulations incorporated in the proposed computer program are the extension of Biot's two phase theory to non-linear region. Numerical study using the program is carried out to demonstrate the three dimensional features of the program and to show the effects of pore water on the dynamic response of underground openings in saturated rock masses. It is shown that underground openings in saturated porous media could be significantly more vulnerable to the potential damages associated with high motions and shear failure that those in dry media.
Keywords: Dynamic response; Saturated rock mass; Two phase theory; Explosive load; Source analysis; Tunnel analysis